Development of novel adsorbent-mangrove-alginate composite bead (MACB) for removal of Pb(II) from aqueous solution - Abas, Siti Nur Aeisyah; Ismail, Mohd Halim Shah; Siajam, Shamsul Izhar; Kamal, Md Lias (Elsevier, 2015)
This study described a preparation of novel composite adsorbent for heavy metal removal by immobilized mangrove bark into alginate as supporting matrix. The removal of Pb(II) ions from aqueous solution by mangrove-alginate composite bead (MACB) was investigated by performing batch adsorption studies to evaluate the performances of the bead. It was found that the adsorption of Pb(II) ions by MACB beads was pH dependent, as the maximum percentage removal was obtained at pH 5.0. The results revealed the superior parameters of MACB beads had attained about 99.15% efficiency in conditions of 7 g L−1 MACB concentration, 150 min contact time, 5.0 as the initial pH, and 250 rpm agitation speed. The adsorption kinetic data can be well described using pseudo-second-order model and the equilibrium data were fitted well by Freundlich isothermal model, respectively. Thermodynamic parameters were calculated and revealed that the adsorption process is an exothermic and spontaneous reaction within range of temperature of 35–65 °C. This indicates that the MACB beads can be used as a promising adsorbent for removal of heavy metals from aqueous solutions.